Desain dan Analisa Mesin Pencacah Nilam Dengan Kapasitas 200 Kg/Jam - Miswan, Miswan; Salimin, Salimin; Endriatno, Nanang (Teknik Mesin Universitas Halu Oleo, 2021)
The Southeast Sulawesi region, which is the East Kolaka area, especially the AERE sub- district, AERE village is an area whose livelihood is in agriculture. One of them is patchouli farming. In processing patchouli, most still use traditional methods. This makes the patchouli processing process less efficient, so researchers want to create a tool that can make patchouli processing to save costs. Patchouli chopping machine is an important tool in improving the observation of patchouli farming. The working principle of this machine utilizes the power of a gasoline motor. Through the Puly mechanism and the V- belt produced by the gasoline motor, it will be transferred to the shaft which is connected to the blade. The stages of design and calculation on the patchouli chopping machine consist of calculating the design power, calculating the shaft, calculating the shear stress, torsional moment of the plan, designing the blade by taking into account the characteristic data of patchouli, the average patchouli volume and patchouli mass (ms). . Based on the results of the calculation of the characteristics of the patchouli plant with an average height of patchouli 150 cm, diameter of the main stem 12.79 mm and density of 0.112 g cm, it can be concluded that the power of the gasoline motor used is 6.5 hp with a shaft rotation of n1 3600 rpm , the design power obtained on the shaft design of the patchouli chopping machine is 9.554 (kw), the shear stress on the shaft is 1.646 kg/mm², the compressive strength of the slicing knife is 36.2044512 N, with a shear stress of 0.1153008 N/mm².Keywords: Design, analysis, crusher machine,patchouli